PENGARUH KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Masyita, Sitti; Lero, Yunita Yusti (Patria Artha Journal of Accounting dan Financial Reporting, 2022)
This study aims to determine the effect of investment decisions and dividend policies on the value of LQ45 companies listed on the Indonesia Stock Exchange. In this study the method used is a quantitative method. The population in this study amounted to 45 companies listed on the Indonesia Stock Exchange. The research sample selected was 36 companies listed on the Indonesia Stock Exchange in 2021. The results of this study indicate that the results of this study indicate that the dividend policy proxied by the Divident Payout Ratio (DPR) has no effect on firm value.